Anomalous fading in thermoluminescence signal of ten different K-feldspar samples and correlation to structural state characteristics. (July 2022) - Polymeris, G.S.; Giannoulatou, V.; Paraskevopoulos, K.M.; Pagonis, V.; Kitis, G.
Abstract: The present work reports an extended study of anomalous fading (AF) in the TL signal of ten different pure K-feldspar samples from North Greece. A fading protocol was applied, including a standard series of TL measurements undertaken following a variety of storage times after irradiation, in order to plot the luminescence output as a function of storage time. Anomalous fading was found to be ubiquitous for the TL signal of all feldspars. The remnant signals are defined as the ratio of the TL signal remaining after storage time t, over the corresponding signal promptly measured. Two different fading rates were calculated, namely the value of g-factor which describes the luminescence signal loss in terms of percentage per decade of time as well as the g50 -factor which describes the fading rate when the signal has been reduced to 50% of the prompt value measured after irradiation due to AF. Both aforementioned fading factors were calculated over the entire TL glow curves in step intervals of 10 °C and were eventually plotted versus glow curve temperature. The analysis indicated that fading factors yield maximum values within the temperature range between 200 and 350 °C, with a tendency to decrease with increasing temperature along the rest glow curve. As the 10 K-feldspar samples belong to three different groups (microclines, sanidines and orthoclases), possible correlation is studied between the fading factors and specific structural parameters of alkali feldspars, such as the probability of Al-cation to occupy specific sites in the forming tetrahedra and the volume of the unit cell. Highlights: Fading study for various K-feldspar samples. Fading rates g and g50 (%/decade) were calculated in interval steps of 10 °C between 150 and 500 °C. Sanidines yield more intense anomalous fading while microclines yield weak anomalous fading. Discrimination among the three different groups could be achieved using the g fading factor but not the g50 factor.